2022
DOI: 10.3389/fpubh.2022.1018686
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up conditions of care and associated factors among adult hypertensive patients during COVID-19 at West Arsi public health facilities, Southeastern Ethiopia: A multi-center cross-sectional study

Abstract: BackgroundCoronavirus disease (COVID-19) is a viral-borne infection caused by the SARS-CoV-2 virus. Aside from the morbidity and mortality effects, it leaves the majority of hypertensive patients untreated and vulnerable to uncontrolled hypertension.ObjectiveThe purpose of this study was to assess follow-up conditions of care and its associated factors among adult hypertensive patients during COVID-19 in public health facilities of West Arsi, Southeastern Ethiopia.MethodsA health facility-based retrospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Negative emotions in psychological factors were among the important issues disrupting the continuity of care for patient with chronic disease. According to the studies of Hiko et al, 22 Moges et al, 23 and Bellini et al, 36 fear, dissatisfaction, stigma, and anxiety were among the factors that had a negative impact on the management of patients with chronic disease during Covid‐19 26 . A study showed quarantine caused depression and anxiety in the elderly 43 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Negative emotions in psychological factors were among the important issues disrupting the continuity of care for patient with chronic disease. According to the studies of Hiko et al, 22 Moges et al, 23 and Bellini et al, 36 fear, dissatisfaction, stigma, and anxiety were among the factors that had a negative impact on the management of patients with chronic disease during Covid‐19 26 . A study showed quarantine caused depression and anxiety in the elderly 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Age was another cause of disruption in the continuity of care in individual and social factors. Old age decreased continuity of care among patients with chronic disease 22–25,36 . A study showed the elderly missed a follow‐up appointment with a doctor 23 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations